Local Investigators Significantly Overestimate Overall Response Rates Compared to Blinded Independent Central Reviews in Uncontrolled Oncology Trials: A Comprehensive Review of the Literature - Dello Russo, Cinzia; Navarra, Pierluigi (Frontiers in Pharmacology, 2022)
Several drugs gained market authorization based on the demonstration of improved progression free survival (PFS), adopted as primary end point in Phase 3 clinical trials. In addition, an increasing number of drugs has been granted accelerated approval, and sometimes regular approval, by the main regulatory agencies based on the evaluation of the overall response rate in Phase 1-2 clinical trials. However, while the overall survival is an unbiased measure of drug efficacy, these outcomes rely on the assessment of radiological images and patients’ categorization using standardized response criteria. The evaluation of these outcomes may be influenced by subjective factors, particularly when the analysis is performed locally. In fact, blinding of treatment is not always possible in modern oncology trials. Therefore, a blinded independent central review is often adopted to overcome the problem of expectation bias associated with local investigator assessments. In this regard, we have recently observed that local investigators tend to overestimate the overall response rate in comparison to central reviewers in Phase 2 clinical trials, whereas we did not find any significant evaluation bias between local investigators and central reviews when considering progression free survival in both Phase 2 and 3 trials. In the present article we are trying to understand the reasons behind this discrepancy by reviewing the available evidence in the literature. In addition, a further analysis of Phase 2 and 3 clinical trials that included the evaluation of both end points showed local investigators significantly overestimate overall response rates compared to blinded independent central reviews in uncontrolled oncology trials.